A platinum complex and its preparation method and application in lenses
By designing the star structure of the platinum complex, using palladium catalytic coupling reaction to synthesize and optimize its ground state absorption in the visible light region, the problems of low transmittance and aggregation of existing light-limiting materials are solved, and high transmittance is achieved The balance of properties and optical limiting properties is suitable for the preparation of new solid-state optical limiting devices.
Patent Information
- Application Number
- CN202211177924.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-09-26
AI Technical Summary
The existing optical limiting materials have low transmittance in the visible light area and are prone to aggregation, which is not conducive to processing and preparation into solid-state devices, and it is difficult to achieve a balance between light transmittance and optical limiting performance.
Using platinum complex, platinum-chlorine complexes are synthesized through palladium-catalyzed Negishi and Sonogashira coupling reactions, and a platinum complex with a star-shaped structure is obtained through base-catalyzed dehydrogenation reactions. The molecular structure is reasonably designed to optimize the visible light region. Ground state absorption.
The high light transmittance and prominent optical limiting properties of the platinum complex in the visible light region are achieved, with wide protection bands, good stability, and easy to process into devices, and are used to prepare hybrid polymers with excellent optical limiting and mechanical properties. lens.
Smart Images

Figure CN115611950B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical limiting materials, and in particular relates to a platinum complex and a preparation method thereof and application thereof in lenses. Background Art
[0002] Laser technology is an important technology widely used in the current cutting-edge science and technology field. It has now penetrated into various fields and industries, and has been widely promoted and applied by all walks of life and developed rapidly. However, the accompanying laser safety issues are often overlooked. Lasers have high energy and strong penetration, which can easily cause laser thermal damage and irreversible damage to human eyes and optical instruments. The damage threshold of the human eye is 0.1μJ. Therefore, the research and development of optical limiting materials and devices that have a protective effect on lasers has become one of the current hotspots. Optical limiting materials are a type of optical material that has high transmittance under low-energy laser radiation and decreased transmittance under high-energy laser radiation. They can effectively protect human eyes and optical instruments from laser damage.
[0003] In recent years, the research on optical limiting materials has developed rapidly. Various inorganic semiconductors, organic small molecules, metal complexes, and carbon materials have been widely used in the research of optical limiting. However, metal phthalocyanine / porphyrin, carbon materials, etc. have strong absorption in the visible light region, low transmittance, and are prone to aggregation, which is not conducive to processing and preparing into solid-state devices. Platinum complexes have rich photophysical properties and excellent optical limiting properties. More importantly, through reasonable molecular design, the ground state absorption of platinum complexes in the visible light region can be optimized to achieve a balance between transmittance and optical limiting performance.
[0004] There are few reports on the preparation of hybrid polymer devices with optical limiting properties by doping optical limiting materials into flexible polymer matrices. This device not only has strong mechanical properties and wide-band optical limiting performance, but also exhibits very excellent optical transmittance in the visible light region. It has good application prospects in the field of optical limiting and is expected to be prepared into a new type of solid-state optical limiting device that is easy to carry. Summary of the invention
[0005] The invention provides a platinum complex and a preparation method thereof and application in lenses. The synthesis method has the characteristics of mild conditions, good yield and the like. The prepared platinum complex has weak ground state absorption in a solution in the visible light region, good light transmittance, outstanding optical limiting properties, a wide protection band, good stability and is easy to be processed into devices. The platinum complex is applied to a hybrid polymer lens with optical limiting performance, the transmittance of the lens in the visible light region reaches more than 85%, and the lens has excellent optical limiting and mechanical properties.
[0006] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0007] A platinum complex having a star-shaped structure, the structural formula is as follows:
[0008]
[0009] in, for The R1 group is The R2 group is an alkyl chain having 1 to 12 carbon atoms.
[0010] The preparation method of the above platinum complex comprises the following steps:
[0011] (1) The s-triazine core and the benzene ring core were synthesized by palladium-catalyzed Negishi and Sonogashira coupling reactions, respectively;
[0012] (2) The raw materials 6a-c are sequentially subjected to Sonogashira coupling, deprotection of the TMS group, and coupling reaction catalyzed by cuprous iodide to synthesize a platinum chloride complex;
[0013] (3) using the platinum chloride complex described in step (2) and the s-triazine core or benzene ring core described in step (1) to undergo a base-catalyzed dehydrohalogenation reaction to obtain a platinum complex;
[0014] The specific synthetic route is as follows:
[0015]
[0016] In the above steps, in the palladium-catalyzed Negishi and Sonogashira coupling reactions in step (1), the catalyst is bistriphenylphosphine palladium chloride or tetrakistriphenylphosphine palladium, preferably tetrakistriphenylphosphine palladium, and the molar ratio of the catalyst to the raw material is 0.05:1; the reaction time is 3 to 24 hours, preferably 3 to 10 hours, and more preferably 5 to 10 hours; the solvent used in the Negishi coupling reaction is dry tetrahydrofuran, and the temperature is 20 to 50°C, preferably 30°C; the solvent used in the Sonogashira coupling reaction is triethylamine, and the temperature is 60 to 90°C, preferably 65°C;
[0017] The raw material 6a-c of the Sonogashira coupling reaction in step (2) is a derivative of carbazole, fluorene or naphthylimide; the reaction time is 12 to 24 hours, and the reaction temperature is 80 to 90° C., preferably 85° C.;
[0018] In step (2) of deprotection of the TMS group, the solvent is a tetrahydrofuran / methanol mixed solvent, the volume ratio of tetrahydrofuran to methanol is 1 to 3:1, preferably 2:1; the inorganic base is potassium carbonate, the molar ratio of potassium carbonate to the raw material is 3 to 10:1, preferably 5 to 8:1.
[0019] In the coupling reaction catalyzed by cuprous iodide in step (2), the cuprous iodide is of analytical purity and is used in an equivalent of 0.03 to 0.10 equivalents; the inert gas atmosphere is nitrogen or argon, preferably argon.
[0020] In the base-catalyzed dehydrohalogenation reaction of step (3), the base used is triethylamine or diisopropylethylamine, preferably triethylamine; the solvent is dichloromethane, and the volume ratio of dichloromethane to triethylamine is 1 to 3:1, preferably 1 to 2:1, and more preferably 1:1; the reaction temperature is 30 to 80° C., preferably 40 to 60° C., and more preferably 50° C.; the reaction time is 12 to 36 h, preferably 20 to 30 h.
[0021] The platinum complex is purified by washing, extraction, drying, and column chromatography. Distilled water is used for washing, petroleum, ethyl acetate or dichloromethane is used for extraction, and the mixture is dried over anhydrous sodium sulfate. Column chromatography uses a column chromatography method known in the art, the mesh size of the silica gel is 200-300 mesh, and the eluent is petroleum ether and dichloromethane.
[0022] The platinum complex is used to prepare a hybrid polymer lens, and the preparation method thereof comprises the following steps:
[0023] (a) weighing a certain amount of a platinum complex and dissolving it in a conventional organic solvent to obtain a solution;
[0024] (b) mixing the solution of step (a) into a polymer matrix, adding a curing agent, and stirring to make the sample solution uniformly mixed, wherein the polymer matrix is polydimethylsiloxane (PDMS); the mass of the platinum complex accounts for 0-0.30% of the total mass of the mixture.
[0025] (c) pouring the sample solution described in step (b) into a mold, volatilizing the solvent, heating and curing in vacuum, and demolding to obtain a hybrid polymer lens, wherein the mold is a circular mold.
[0026] The content of the platinum complex in step (a) is 0 to 50 mg, preferably 0 to 33 mg, more preferably 10 to 30 mg;
[0027] The conventional organic solvent in step (a) is dichloromethane, tetrahydrofuran, toluene, etc., preferably dichloromethane with a low boiling point;
[0028] In step (b), the polymer matrix is polydimethylsiloxane purchased from Dow Corning, USA, the mass of polydimethylsiloxane is 10 g, and the ratio of polydimethylsiloxane to curing agent is 5 to 15:1, preferably 8 to 12:1, and more preferably 10:1;
[0029] In step (c), the circular mold is a polymer mold or a glass mold, preferably a glass mold; the vacuum curing temperature is 60 to 120°C, preferably 80 to 100°C, more preferably 80°C; the vacuum curing time is 2 to 24 hours, preferably 4 to 10 hours. The most preferred curing conditions are: continuous curing at 80°C in vacuum for 5 hours.
[0030] There is no particular limitation on demoulding in step (c), and a method familiar to those skilled in the art may be used. In the present invention, a stainless steel scraper is used for forced demoulding.
[0031] The present invention has no special limitation on the mixing method, and any mixing method known to those skilled in the art can be used, preferably magnetic stirring, with a stirring speed of 500 to 1000 rpm, preferably 600 to 800 rpm.
[0032] The present invention provides a platinum complex and a preparation method thereof and an application in a lens. The platinum complex has excellent light transmittance in the visible light region and outstanding light limiting properties. The platinum complex has good solubility and is easy to be processed into a device. The hybrid polymer lens prepared by doping the platinum complex into polydimethylsiloxane has very excellent light limiting performance at 532nm. At the same time, the lens also has good light transmittance, flexibility and aging resistance, and can be used as a new type of solid-state light limiting device.
[0033] Beneficial effects: The present invention provides a platinum complex and a preparation method thereof and an application in lenses. By precisely regulating the molecular structure, the platinum complex has high optical transmittance in the visible light region and has a wide-band optical limiting property. The introduction of a long alkyl chain improves the solubility of the platinum complex, making it easy to process and prepare into a device. The platinum complex is doped into a polymer matrix and a hybrid polymer lens is prepared by thermal curing. Compared with the prior art, this method has the advantages of short time consumption, low cost, and suitability for mass production. The prepared hybrid polymer lens has very excellent optical limiting performance at 532nm, and the lens also has good light transmittance. The transmittance of the lens in the visible light region is more than 85%, and the optical limiting performance is outstanding. By adjusting the doping concentration of the platinum complex, the optical, mechanical, thermal and other properties of the lens can be regulated. The lens has good mechanical properties and photothermal stability, can be used as a new type of solid-state optical limiting device, and has great practical value in the field of optical limiting. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a process flow chart for preparing the platinum complex of the present invention;
[0035] Figure 2 is a process flow chart of the preparation of the hybrid polymer lens of the present invention;
[0036] Figure 3 These are actual photos of Pt-2b@PDMS lenses with different doping concentrations of the present invention;
[0037] Figure 4 The figure shows the mechanical properties of the Pt-2b@PDMS lens with different doping concentrations of the present invention;
[0038] Figure 5 It is the UV-visible absorption spectrum of the platinum complexes Pt-1a to Pt-2c of the present invention in toluene solution;
[0039] Figure 6 It is an emission spectrum diagram of the platinum complexes Pt-1a to Pt-2c of the present invention in a degassed toluene solution;
[0040] Figure 7 The nanosecond transient absorption spectra of the platinum complexes Pt-1b, Pt-1c, Pt-2b and Pt-2c of the present invention in a degassed toluene solution;
[0041] Figure 8 It is the open pore Z-scan curve of the toluene solution of the platinum complexes Pt-1a to Pt-2c of the present invention measured at 532 nm;
[0042] Fig. 9 It is the optical limiting curve of the toluene solution of the platinum complexes Pt-1a to Pt-2c of the present invention measured at 532nm;
[0043] Fig.10 : is the linear transmittance curve of the Pt-2b@PDMS lens with different doping concentrations of the present invention;
[0044] Fig.11 : This is the optical limiting curve of the Pt-2b@PDMS lens with different doping concentrations at 532nm of the present invention. DETAILED DESCRIPTION
[0045] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments:
[0046] A platinum complex having a structure shown in formula I:
[0047]
[0048] in, for One of the following, the R1 group is The R2 group is an alkyl chain having 1 to 12 carbon atoms.
[0049] like Figure 1 As shown, the above-mentioned platinum complex preparation method comprises the following steps:
[0050] Synthesis of compound 2
[0051]
[0052] Under argon atmosphere, trimethylethynylsilane (0.49 g, 5 mmol) was dissolved in 15 mL of dry tetrahydrofuran solution, cooled to -78 ° C, and n-butyl lithium (2.0 mL, 2.5 M in Hexane) was slowly added dropwise. After the addition was complete, stirring was continued for 40 minutes, and then zinc chloride solution (10 mL, 0.5 M in THF) was slowly added dropwise. After the addition was complete, the low temperature was turned off, and the reaction solution naturally warmed to room temperature and stirred for 3 hours. Cyanuric chloride (0.18 g, 1 mmol) and tetrakistriphenylphosphine palladium (58 mg, 0.05 mmol) were dissolved in 5 mL of dry tetrahydrofuran solution and then added to the above reaction solution. The mixed system was reacted at 30° C. for 5 hours. After the reaction was completed, 50 mL of dilute hydrochloric acid and ethyl acetate were added, and the liquid was extracted. The organic layer was washed with saturated brine, dried over anhydrous sodium sulfate, and the solvent was removed by distillation under reduced pressure to obtain a black oily liquid. The crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether / dichloromethane = 10 / 1) to obtain a white solid (yield: 69%);
[0053] Synthesis of compound 5
[0054]
[0055] Under argon atmosphere, 1,3,5-tribromobenzene (1.57 g, 5 mmol) was dissolved in 50 mL of triethylamine solution, and bistriphenylphosphine palladium chloride (0.17 g, 0.25 mmol) and cuprous iodide (28 mg, 0.15 mmol) were added. The system was stirred at 40 ° C for 30 minutes, and then trimethylethynylsilane (2.95 g, 30 mmol) was slowly injected, and the mixed system was further reacted at 65 ° C for 5 hours. After the reaction was completed, it was cooled to room temperature, and the solvent was removed by vacuum distillation to obtain a black solid. The crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether) to obtain a yellow solid;
[0056] The above yellow solid (0.70 g, 2 mmol) was dissolved in 20 mL of tetrahydrofuran and 10 mL of methanol solution, potassium carbonate (1.50 g, 12 mmol) was added, and the mixed system was stirred at room temperature for 5 hours. After the reaction, petroleum ether and distilled water were added, and the liquid was extracted. The organic layer was dried over anhydrous sodium sulfate and the solvent was removed under reduced pressure to obtain a light yellow solid. The crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether) to obtain a white solid (yield: 77%).
[0057] Synthesis of compound 7a
[0058]
[0059] Compound 6a (6 mmol), bistriphenylphosphine palladium chloride (0.30 mmol), triphenylphosphine (0.30 mmol), cuprous iodide (0.06 mmol) and 40 mL of triethylamine were added to a 100 mL two-necked flask, the system was replaced with argon three times, and then trimethylethynylsilane (0.98 g, 10 mmol) was slowly added, and the mixed system was stirred at 85° C. overnight. After the reaction was completed, it was cooled to room temperature, and the solvent was removed by distillation under reduced pressure. The crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether / dichloromethane) to obtain a yellow oily liquid (yield: 85%).
[0060] Synthesis of compound 7b
[0061]
[0062] The amount of reactants and the reaction process were the same as those for the synthesis of 7a, except that compound 6a was replaced by 6b. A yellow oily liquid was obtained after purification (yield: 76%).
[0063] Synthesis of compound 7c
[0064]
[0065] The amount of reactants and the reaction process were the same as those for the synthesis of 7a, except that compound 6a was replaced by 6c, and a brown solid was obtained by purification (yield: 72%).
[0066] Synthesis of compound 8a
[0067]
[0068] Phase compound 7a (5 mmol), potassium carbonate (50 mmol), 30 mL of tetrahydrofuran and 15 mL of methanol solution were added to a 100 mL two-necked flask, and the mixed system was stirred at room temperature for 5 hours. After the reaction was completed, suction filtration was performed, ethyl acetate and distilled water were added to the filtrate, and the liquid was separated by extraction. The organic layer was dried over anhydrous sodium sulfate and the solvent was removed under reduced pressure. The crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether / dichloromethane) to obtain a yellow solid (yield: 77%).
[0069] Synthesis of compound 8b
[0070]
[0071] The amount of reactants and the reaction process are the same as those for the synthesis of 8a, except that compound 7a is replaced by compound 7b, and a light yellow oily liquid is obtained after purification (yield: 53%).
[0072] Synthesis of compound 8c
[0073]
[0074] The amount of reactants and the reaction process are the same as those for the synthesis of 8a, except that compound 7a is replaced by compound 7c, and a brown solid is obtained by purification (yield: 90%).
[0075] Synthesis of compound 9a
[0076]
[0077] Under argon atmosphere, the corresponding compound 8a (1 mmol) and trans-[PtCl2(PBu3)2] (1.2 mmol) were dissolved in 50 mL of a mixed solution of deoxygenated tetrahydrofuran and triethylamine (v / v, 1 / 1), and then a catalytic amount of cuprous iodide (0.03 mmol) was added, and the system was reacted at room temperature for 12 hours. After the reaction was completed, the solvent was removed by distillation under reduced pressure, the residue was dissolved in dichloromethane, washed with distilled water, extracted and separated, the organic layer was dried over anhydrous sodium sulfate, the solvent was removed under reduced pressure, and the crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether / dichloromethane) to obtain a yellow oily liquid (yield: 56%).
[0078] Synthesis of compound 9b
[0079]
[0080] The amount of reactants and the reaction process were the same as those for the synthesis of 9a, except that compound 8a was replaced by compound 8b, and a light yellow oily liquid was obtained after purification (yield: 77%).
[0081] Synthesis of compound 9c
[0082]
[0083] The amount of reactants and the reaction process were the same as those for the synthesis of 9a, except that compound 8a was replaced by compound 8c, and a light yellow solid was obtained by purification (yield: 41%).
[0084] Synthesis of Platinum Complex Pt-1a
[0085] Compound 9a (0.75 mmol) was dissolved in 40 mL of a mixed solution of dichloromethane and triethylamine (v / v, 1 / 1). After deoxygenation for 30 minutes, compound 5 (30 mg, 0.2 mmol) and cuprous iodide (-8 mg) were added, and the mixture was stirred at 50°C for 24 hours under an argon atmosphere. After the reaction was completed, the solvent was removed by distillation under reduced pressure, the residue was dissolved in dichloromethane, washed with distilled water, extracted and separated, the organic layer was dried over anhydrous sodium sulfate, the solvent was removed under reduced pressure, and the crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether / dichloromethane) to obtain a light yellow solid (yield: 69%).
[0086] H NMR spectrum data of platinum complex Pt-1a: 1 H NMR (400MHz, CDCl3) δ8.04–7.98(m,6H),7.46–7.39(m,6H),7.36(d,J=8.1Hz ,3H),7.20(dd,J=14.9,7.4Hz,6H),7.00(s,3H),4.25(t,J=7.2Hz,6H),2.19( dt,J=7.8,3.9Hz,36H),1.87–1.82(m,6H),1.71–1.58(m,36H),1.48(q,J=7. 3Hz, 36H), 1.40–1.22 (m, 18H), 0.95 (t, J = 7.3Hz, 54H), 0.86 (t, J = 7.0Hz, 9H).
[0087] Synthesis of Platinum Complex Pt-1b
[0088] The amount of reactants and the reaction process are the same as those for the synthesis of Pt-1a, except that compound 9a is replaced by compound 9b. A light yellow solid is obtained by column chromatography purification (yield: 82%).
[0089] H NMR data of platinum complex Pt-1b: 1 H NMR (400MHz, CDCl3) δ7.62(d,J=7.1Hz,3H),7.52(d,J=8.3Hz,6H),7.29(d,J =6.2Hz,9H),7.23(d,J=9.7Hz,6H),6.99(s,3H),2.17(dt,J=7.9,3.8Hz,36H) ,1.97–1.82(m,12H),1.70–1.58(m,36H),1.46(q,J=7.3Hz,36H),1.18–0.99 (m,36H),0.94(t,J=7.3Hz,54H),0.76(t,J=7.2Hz,18H),0.68–0.53(m,12H).
[0090] Synthesis of Platinum Complex Pt-1c
[0091] The amount of reactants and the reaction process are the same as those for the synthesis of Pt-1a, except that compound 9a is replaced by compound 9c. A yellow solid is obtained by column chromatography purification (yield: 53%).
[0092] H NMR spectrum data of platinum complex Pt-1c: 1 H NMR (400MHz, CDCl3) δ8.79(d,J=9.2Hz,3H),8.57(d,J=7.2Hz,3H),8.45(d,J=7.7Hz,3H),7.72–7.57(m,6H),7.03(s,3H),4. 21–4.12(m,6H),2.13(dd,J=9.8,5.7Hz,36H),1.77–1.69(m,6H),1.63(d,J=3.6Hz,36H),1.49–1.30(m,54H),0.91(m,63H).
[0093] Synthesis of Platinum Complex Pt-2a
[0094] Compound 9a (0.75 mmol) and compound 2 (74 mg, 0.2 mmol) were dissolved in 40 mL of a mixed solution of dichloromethane and triethylamine (v / v, 1 / 1). After deoxygenation for 30 minutes, tetrabutylammonium fluoride solution (0.6 mL, 1.0 M in THF) and cuprous iodide (~8 mg) were added, and the mixed system was stirred at 50°C for 24 hours under an argon atmosphere. After the reaction was completed, the solvent was removed by distillation under reduced pressure, the residue was dissolved in dichloromethane, washed with distilled water, extracted and separated, the organic layer was dried over anhydrous sodium sulfate, the solvent was removed under reduced pressure, and the crude product was purified by column chromatography (200-300 mesh silica gel, eluent: petroleum ether / dichloromethane) to obtain a light yellow solid (yield: 50%)
[0095] H NMR spectrum data of platinum complex Pt-2a: 1 H NMR (400MHz, CDCl3) δ8.03–7.97(m,6H),7.44(t,J=7.6Hz,3H),7.37(d,J=8. 1Hz, 6H), 7.21 (dd, J=15.4, 8.0Hz, 6H), 4.26 (t, J=7.2Hz, 6H), 2.07 (dt, J=8.1 ,3.9Hz,36H),1.88–1.82(m,6H),1.60(dt,J=7.5,3.8Hz,36H),1.49(q,J=7.3 Hz,36H),1.37–1.23(m,18H),0.95(t,J=14.5Hz,54H),0.86(t,J=6.9Hz,9H).
[0096] Synthesis of Platinum Complex Pt-2b
[0097] The amount of reactants and the reaction process are the same as those for the synthesis of Pt-2a, except that compound 9a is replaced by compound 9b. A light yellow solid is obtained by column chromatography purification (yield: 58%).
[0098] H NMR spectrum data of platinum complex Pt-2b: 1 H NMR (400MHz, CDCl3) δ7.65–7.60(m,3H),7.53(d,J=8.2Hz,3H),7.32–7.27(m,6H),7.25–7.19(m,9H),2.05(dt,J=8.0,3.9Hz,36H),1.90(qt,J=13. 6,6.7Hz,12H),1.68–1.54(m,36H),1.46(q,J=7.3Hz,36H),1.16–0.98(m, 36H), 0.94 (t, J=7.3Hz, 54H), 0.76 (t, J=7.2Hz, 18H), 0.66–0.51 (m, 12H).
[0099] Synthesis of Platinum Complex Pt-2c
[0100] The amount of reactants and the reaction process are the same as those for the synthesis of Pt-2a, except that compound 9a is replaced by compound 9c. A yellow solid is obtained by column chromatography purification (yield: 65%).
[0101] Platinum complex Pt-2c H NMR spectrum data: 1 H NMR (400MHz, CDCl3) δ8.79–8.73(m,3H),8.57(d,J=6.9Hz,3H),8.45(d,J=7.7Hz,3H),7.66(t,J=7.8Hz,3H),7.59(d,J=7.7Hz, 3H),4.19–4.13(m,6H),2.11(dt,J=7.7,3.7Hz,36H),1.78–1.68(m,6H),1.69–1.56(m,36H),1.44–1.31(m,54H),0.91(m,63H).
[0102] Pt-2b is used as an example to demonstrate the feasibility of doping platinum complexes into flexible polymer matrices to prepare hybrid polymer lenses. The specific preparation process is as follows: Figure 2 As shown:
[0103] Use an electronic balance to accurately weigh a certain mass of Pt-2b (0 mg, 2.2 mg, 5.5 mg, 11 mg, 22 mg, 33 mg), dissolve it in 20 mL of dichloromethane to obtain solutions of different concentrations. At room temperature, mix the solution into 10 g of polydimethylsiloxane (purchased from Dow Corning), stir it with a magnetic stirrer until it is evenly mixed, then add 1.0 g of curing agent and continue stirring for 1 hour. After standing for a while, degas the mixture, then pour it into a circular glass mold with a diameter of 40 mm and a thickness of 2 mm, and leave it at room temperature for a period of time to allow the dichloromethane to completely evaporate. Then, put it in a vacuum drying oven and cure it continuously at 80 degrees Celsius for 5 hours. After curing, cool it to room temperature and carefully demold it to obtain polymer lenses Pt-2b@PDMS with different doping concentrations.
[0104] Figure 3 The actual photos of Pt-2b@PDMS lenses with doping concentrations of 0, 0.02wt%, 0.05wt%, 0.10wt%, 0.20wt%, and 0.30wt% are shown. It can be seen from the figure that within this doping concentration range, the platinum complex has good compatibility with polydimethylsiloxane and is evenly dispersed. The obtained lens has a smooth surface, uniform color, and no damage on the appearance, and can be directly used for optical measurement. Figure 4 The mechanical properties of the Pt-2b@PDMS lens with a doping concentration of 0.05wt% were also demonstrated. After folding and bending, the lens can still return to its original shape, indicating good flexibility.
[0105] The platinum complexes were tested as follows:
[0106] Test Example 1: Absorption spectrum test of platinum complexes Pt-1a~Pt-2c
[0107] Using toluene as solvent, Pt-1a~Pt-2c were prepared to a concentration of 1.0×10 –5 mol / L sample solution. At room temperature, use a TU-1900 UV-Vis spectrophotometer and a 1 cm quartz cuvette to first perform a baseline scan of the toluene solvent (scanning range: 200–800 nm). After subtracting the background, scan the sample solution and measure its UV-Vis absorption spectrum. The results are shown in Figure 5 .from Figure 5 It can be seen that the ground state absorption of these platinum complexes is mainly concentrated in the range of 300-450nm, the absorption peak is mainly attributed to the π-π* transition, the ground state absorption in the visible light region is weak, and has excellent optical transmittance.
[0108] Test Example 2: Emission spectrum test of platinum complexes Pt-1a~Pt-2c
[0109] Using toluene as solvent, Pt-1a~Pt-2c were prepared to a concentration of 1.0×10 –5 mol / L sample solution. Argon was continuously introduced into the solution for 30 minutes to deoxygenate it. Then the sample solution was tested using a Hitachi F-4600 fluorescence spectrophotometer at room temperature. The emission spectrum was as follows: Figure 6 As shown in the figure, except for Pt-2a and Pt-2c, other platinum complexes exhibit dual emission properties at room temperature. The emission peak at a shorter wavelength can be attributed to fluorescence emission, while the emission peak at a longer wavelength can be attributed to phosphorescence emission.
[0110] Test Example 3: Transient absorption spectrum test of platinum complexes Pt-1a~Pt-2c
[0111] Using toluene as solvent, Pt-1a~Pt-2c were prepared into sample solutions with an absorbance A of 0.4 at 355nm. Argon was continuously passed through the solution for 30 minutes at room temperature to remove oxygen, and then the transient absorption spectrum was tested using an Edinburgh LP980 laser flash photolysis instrument (the excitation light source was Nd:YAG laser, wavelength was 355nm). The results are shown in Figure 7 No signals were detected for the two platinum complexes Pt-1a and Pt-2a, while other platinum complexes showed strong positive absorption bands in the range of 450-800nm, indicating that they all have strong excited state absorption in this band. However, Pt-1c and Pt-2c showed obvious bleaching peaks near 425nm, which were caused by their strong ground state absorption at this wavelength.
[0112] Test Example 4: Z-scan test of platinum complexes Pt-1a to Pt-2c
[0113] Pt-1a~Pt-2c were prepared with toluene to a concentration of 5.0×10 –4 mol / L sample solution. Nd:YAG laser was used as the excitation source, and a pulsed laser with a wavelength of 532nm, a pulse width of 5ns, and a repetition frequency of 10Hz was selected. The sample was placed in a 2mm quartz cuvette, and the incident laser energy was adjusted by moving the cuvette to perform a Z-scan test on the sample solution. Figure 8 The Z-scan curve shows that the normalized transmittance decreases with the increase of laser intensity and is the smallest at the focus, showing a typical nonlinear absorption phenomenon. It has a high transmittance under low-intensity laser irradiation and a lower transmittance under high-intensity laser irradiation, indicating that these platinum complexes have good nonlinear absorption properties. Among them, Pt-2b has the best nonlinear absorption properties under the same test conditions.
[0114] Test Example 5: Optical Limiting Performance Test of Platinum Complexes Pt-1a to Pt-2c
[0115] The sample solution was prepared in the same manner as in Test Example 4. Nd:YAG laser was used as the excitation light source, and a pulsed laser with a wavelength of 532nm and a pulse width of 4.1ns was selected. The sample was placed in a cuvette with an optical path of 2mm, and a laser incident energy-transmitted energy test was performed to obtain the optical limiting curve. The test results are shown in Fig. 9 As shown in the figure, as the incident light density gradually increases, the energy density transmitted through the sample has a certain downward trend, among which Pt-1b and Pt-2b have a greater degree of decline, indicating that these two platinum complexes have more prominent light limiting properties and can be used as effective light limiting materials. Under this test condition, Pt-2c did not show obvious light limiting phenomenon.
[0116] Test Example 6: Transmittance curve test of polymer lenses Pt-2b@PDMS with different doping concentrations
[0117] By measuring the UV-visible absorption spectra of lenses with different doping concentrations, and then converting them using the Lambert-Beer law, the transmittance can be obtained. Fig.10 As shown in the figure, the transmittance of the blank PDMS lens in the visible light band is always maintained above 90%, and when the doping concentration is in the range of 0.02-0.30wt%, the transmittance of the lens Pt-2b@PDMS in the 400-800nm band can also be maintained above 85%, which can ensure the visibility of the surrounding environment by the human eye and the reception of normal signals by optical instruments.
[0118] Test Example 7: Optical limiting curve test of polymer lenses Pt-2b@PDMS with different doping concentrations
[0119] The test conditions are the same as those in Test Example 5, except that the sample solution is replaced with a polymer lens during the test. Fig.11 The optical limiting curves obtained by the test show that these lenses have excellent optical limiting performance, and the optical limiting performance is enhanced with the increase of Pt-2b doping concentration. Taking the doping concentration of 0.30wt% as an example, when the incident laser energy density is 2.0J / cm 2 When the output light energy density drops to 0.30J / cm 2 .
[0120] The above description is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A platinum complex, characterized in that The complex structure has a star-shaped structure, and the structural formula is as follows: in, for or ; R1 group is , or ; The R2 group is an alkyl chain having 1 to 12 carbon atoms.
2. The method for preparing the platinum complex according to claim 1, characterized in that: The following steps are involved: (1) The s-triazine core and the benzene ring core were synthesized by palladium-catalyzed Negishi and Sonogashira coupling reactions, respectively; (2) The raw material carbazole, fluorene or naphthylimide derivatives are sequentially subjected to Sonogashira coupling, deprotection of the TMS group, and coupling reaction catalyzed by cuprous iodide to synthesize a platinum chloride complex; (3) using the platinum chloride complex described in step (2) to react with the s-triazine core or the benzene ring core described in step (1) under base catalysis to undergo dehydrohalogenation reaction to obtain a platinum complex.
3. The method for preparing a platinum complex according to claim 2, characterized in that: In the palladium-catalyzed Negishi and Sonogashira coupling reactions in step (1), the catalyst is bistriphenylphosphine palladium chloride or tetrakistriphenylphosphine palladium, and the reaction time is 3 to 24 h; the Negishi coupling reaction temperature is 20 to 50° C.; and the Sonogashira coupling reaction temperature is 60 to 90° C.
4. The method for preparing a platinum complex according to claim 3, characterized in that: The catalyst is tetrakistriphenylphosphine palladium, and the molar ratio of the catalyst to the raw material is 0.05:
1.
5. The method for preparing a platinum complex according to claim 2, characterized in that: The reaction time of the Sonogashira coupling reaction in step (2) is 12-24 hours, and the reaction temperature is 80-90° C.; the solvent for the deprotection of the TMS group is a tetrahydrofuran / methanol mixture, and the inorganic base is potassium carbonate; the equivalent of cuprous iodide used in the coupling reaction catalyzed by cuprous iodide is 0.03-0.10 equivalents.
6. The method for preparing a platinum complex according to claim 5, characterized in that: The volume ratio of tetrahydrofuran to methanol is 1-3:1; the volume ratio of potassium carbonate to raw material is 3-10:
1.
7. The method for preparing a platinum complex according to claim 2, characterized in that: In the base-catalyzed dehydrohalogenation reaction of step (3), the volume ratio of base to solvent is 1-3:1, the reaction temperature is 30-80°C, and the reaction time is 12-36 h.
8. The method for preparing a platinum complex according to claim 2 or 7, characterized in that: The base used is triethylamine or diisopropylethylamine, the solvent is dichloromethane, the reaction temperature is 40~60°C, and the reaction time is 20~30 h.
9. The platinum complex according to claim 1 is used for preparing lenses, characterized in that: The method for preparing the lens comprises the following steps: (a) weighing a certain amount of platinum complex and dissolving it in a conventional organic solvent to obtain a solution; (b) mixing the solution of step (a) into a polymer matrix, adding a curing agent, wherein the mass ratio of the polymer matrix to the curing agent is 5 to 15:1, and stirring to make the sample solution uniformly mixed; (c) Pour the sample solution described in step (b) into the mold, evaporate the solvent, heat and cure at 60-120° C. in vacuum for 2-24 h, and demold to obtain the hybrid polymer lens.
10. The platinum complex according to claim 9 is used for preparing lenses, characterized in that: The content of the platinum complex in the lens is 0.02 wt % to 0.30 wt %.
Citation Information
Patent Citations
Platinum metal gel material and preparation method and application thereof
CN110066298A
Self-repairing platinum metal gel material, preparation method and application thereof
CN113666969A